Frontispiece: Ligand‐Controlled Doping Effects in Alloy Nanoclusters Au4Ag23 and Au5Ag24. Issue 60 (29th October 2018) - Du, Yang; Guan, Zong‐Jie; Wen, Zhao‐Rui; Lin, Yu‐Mei; Wang, Quan‐Ming
Abstract : The Frontispiece shows two nanoclusters are induced by the change of the surface alkynyl structures. The alkynyl −C≡C− t Bu gives rise to a more spherical surface shape in1 (red background) while −C≡CC6 H4 ‐ p ‐ t Bu to a flat shape in2 (green backgroud). The red and green also represent their different crystal colors and different UV/Vis properties. There are also Cl (green ball) and dppf (purple ball) surrounding these structures, suggesting co‐protection by three types of ligands. For more information, see the Full Paper Y.‐M. Lin, Q.‐M. Wang et al. onpage 16029 ff.